Tinjauan Etika Mengenai Kode Etik Profesi Hakim Dalam Menggunakan Media Sosial - Tiara Rachma Sari; Kayus Kayowuan Lewoleba (Madani: Jurnal Ilmiah Multidisiplin, 2023)
With the rapid development of technology, it is now easier for people to communicate and find information, one of which is through social media. Social media has various types, advantages and disadvantages. The use of social media is not limited to a person's status, such as age, gender, religion or profession. Currently, many judges use social media to communicate, seek information and interact with the public. However, the use of social media by judges can affect public trust in the judiciary. In several countries, there are already rules and ways for judges to use social media properly and correctly. However, in Indonesia, the Code of Ethics and Code of Conduct for Judges (KEPPH) which has been in effect since 2009 does not regulate the use of social media by judges. Therefore, this research aims to assist the Supreme Court and the Judicial Commission in creating regulations or guidelines regarding the use of social media by judges, as well as assisting judges in using social media without violating the judge's professional code of ethics.